Entre l’arbre et l’écorce : la recherche criminologique au Canada (1960-1985) - Szabo, Denis (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1986)
The author describes the relationship that has been established over the past 25 years between university centres doing research in criminology and the Federal Government, pointing out both areas of agreement and as an expert and participant in the field, advocates a pluralistic type of collaboration between the University and the public authorities.